2011
DOI: 10.1007/s11523-011-0199-0
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary toxicities from targeted therapies: a review

Abstract: Pulmonary toxicity is rarely seen with most commonly used targeted therapies. The endothelial growth factor receptor (EGFR) small-molecule tyrosine kinase inhibitors (TKIs) gefitinib and erlotinib can cause interstitial lung disease (ILD). BCR-ABL tyrosine kinase inhibitors imatinib and dasatinib can cause pleural effusions. Infusion-related bronchospasm is common with the monoclonal antibodies to EGFR cetuximab and panitumumab, and case reports of bronchiolitis and pulmonary fibrosis have been described. Up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 86 publications
(97 reference statements)
1
53
0
8
Order By: Relevance
“…Pour les thérapies ciblées, le gefitinib agirait sur des mécanismes de régénération (réparation) de l'épithélium alvéolaire favorisant la survenue de PM [14,28], le dasatinib ciblerait la voie du PDGF (Platelet Derived Growth Factor) favorisant la survenue d'une hypertension artérielle pulmonaire [10,11]. La toxicité des inhibiteurs des points de contrôle immunitaire résulte possiblement d'une réaction exagérée de l'auto-immunité.…”
Section: Quels Médicaments ?unclassified
See 1 more Smart Citation
“…Pour les thérapies ciblées, le gefitinib agirait sur des mécanismes de régénération (réparation) de l'épithélium alvéolaire favorisant la survenue de PM [14,28], le dasatinib ciblerait la voie du PDGF (Platelet Derived Growth Factor) favorisant la survenue d'une hypertension artérielle pulmonaire [10,11]. La toxicité des inhibiteurs des points de contrôle immunitaire résulte possiblement d'une réaction exagérée de l'auto-immunité.…”
Section: Quels Médicaments ?unclassified
“…• la liste des médicaments susceptibles de se compliquer d'IRAM s'étoffe régulièrement (Tableaux 1-3) [3,[10][11][12][13][14][15]. Mais tous les médicaments ne sont pas responsables d'IRA avec la même fréquence ;…”
Section: Introductionunclassified
“…In addition, RAPA is used to prevent rejection following organ transplantation, with few side effects. In previous studies, RAPA demonstrated antitumor activity, in addition to specific autophagy inhibition (12)(13)(14). The present study aimed to investigate the combined biological effect of TMZ and RAPA on the proliferation, survival, apoptosis, cell cycle distribution and autophagy of cerebral glioma cells, and the underlying molecular mechanisms involved, in order to develop more effective treatments for patients with glioma.…”
Section: Introductionmentioning
confidence: 96%
“…Akciğer kanseri tedavisi için güncel algoritmaların kullanılması, agresif cerrahi yöntemler, kemoterapi ve radyoterapi modalitelerinin birlikte kullanımıyla cerrahi için uygun olmayan hastalarda dahi 5 yıllık sağkalım %16'ya ulaşmıştır (5,6). Bu durum; gerek hastalığın kendine, gerekse radyasyon terapisi, tirozin kinaz inhibitörleri gibi tedavilerle ilişkili komplikasyonlara ve komorbiditelere bağlı durumların daha sık karşımıza çıkmasına neden olmuştur (7,8). Başta akut solunum yetmezliği olmak üzere bu hasta grubunun yoğun bakım ihtiyacı ve yoğun bakım ünitelerine (YBÜ) kabulü artmıştır (9).…”
Section: Introductionunclassified